Modeling regional cumulative effects of land use and land cover variations in relation to persistence of the Persian leopard (Panthera pardus saxicolor) in Iran - Sanei, Arezoo (2018)
Cumulative effect of land use and land cover changes on the persistence of the Persian leopard (Panthera pardus saxicolor) in Iran is not characterized and formulated so far. Current research is concerned with developing an innovative species and region specific methodological approach to predict cumulative effect of the land use and land cover variations on the Persian leopard persistence. The research is a countrywide practice conducted in a regional basis in Iran with three provinces selected for the relative ground validation techniques. Accordingly, three main research sections are developed to assess the data and information required for formulation of the models. In the first section the provinces are innovatively classified into five significantly dissimilar regions in terms of environmental variations based on the wide distribution of the Persian leopard in at least 30 out of 31 provinces of Iran. Sufficient well distributed leopard presence records together with 17 natural and human variables were used to develop potential habitat predictive maps in a regional basis using MaxEnt software. Variables are tested for possible correlation among them and models were evaluated for the predictive performance. The research null hypothesis regarding no significant regional variability of permutation importance of the research variables in the best fitted predictive models, is accepted. Two landscape corridors to improve the leopard distribution pattern connectivity in a metapopulation scale are identified. The next research section is aimed to validate the developed best fitted predictive models in the earliest section via ground validation techniques to eventually assess a threshold value indicating the minimum suitability rate for the leopard presence. In this regards, three threshold rules including equal training sensitivity and specificity, maximum training sensitivity plus specificity and minimum training presence were selected for the purpose of binary classification of the predictive maps. Accordingly, field surveys (e.g. camera trapping for 2,541 trap nights, sign surveys, interviews with local knowledgeable people) together with mapping and overlays concentrated on the errors of omission across three selected provinces in (1) North-East containing Kopet Dag Mountains, (2) North-West located in the Caucasus Ecoregion and (3) adjacent to the Persian Gulf in southernmost part of the leopard range in the country. The results indicate that the sensitivity and specificity based threshold rules show more accuracy comparing to the minimum training presence rule with notable overestimation of the suitability rates. Eventually, habitat suitability rate of 0.3 on the developed predictive maps was identified as a value to safely recognize the actual potential habitats with confirmed significance for conservation planning. The latest section of the research is aimed to develop empirically fitted species and region specific models and relative threshold values using the findings of previous research sections to assess cumulative effects of land use and land cover variables on the regional persistence of the Persian leopard. The Principle Component Analysis and regression curve estimation were used as the main statistical techniques in this section. Two types of innovative models with relative threshold values were developed. The first type uses habitat suitability rates while the second type uses density of the land use and land cover variables. Subsequently, current status of each province in relation to the Persian leopard regional persistence is assessed. Accordingly, adjustments are required in cumulative effect of land use and land cover variables to improve the quality of two identified landscape corridors in the earliest section as their current status is significantly farther than the threshold level to ascertain regional persistent of the Persian leopard. Findings of this research support the earlier hypothesis indicating that the leopard range in Iran is in the process of splitting to the northern and southern fragmented parts. Research sections developed in this study contribute significantly to the current knowledge about the Persian leopard status and the conservation requirements. The developed approach provides a helpful insight to the decision makers to wisely consider wildlife friendly solutions for development activities and prevent negative cumulative effect of land use and land cover changes on leopard persistence in each region. These innovative models can be adjusted to be used for the conservation purposes in other countries of the Persian leopard range in southwest Asia. The approach can be used to develop similar species and region specific models addressing other regions and large cat species.